Clinical and microbiological features of host-bacterial interplay in chronic venous ulcers versus other types of chronic skin ulcers - Mihai, Mara Mădălina; Popa, Mircea Ioan; Holban, Alina Maria; Gheorghe-Barbu, Irina; Popa, Liliana Gabriela; Chifiriuc, Mariana-Carmen; Giurcăneanu, Călin; Bleotu, Coralia; Cucu, Corina Ioana; Lazăr, Veronica (Frontiers in Microbiology, 2024)
Chronic venous ulcers of the lower limbs develop in the context of advanced venous disease and have a significant impact on the patient’s quality of life, being associated with depression and worrisome suicide rates, as well as with an economic burden due to increased medical care costs and an epidemiologic risk due to healthcare associated infections and the emergence of strains resistant to multiple classes of antibiotics and/ or antiseptics. Although numerous studies have investigated the composition of the microflora of chronic wounds, either by classical diagnostic methods or by combining molecular methods, there are no comparative data on the virulence and resistance profiles of strains isolated from venous ulcers with the manifested clinical picture. The elucidation of pathogenic mechanisms, at the molecular level, is crucial in the fight against these important human microbial agents, in order to discover new therapeutic targets. In this study we aimed to characterize the phenotypic virulence profiles (including the ability to develop biofilms) of microorganisms isolated from chronic skin wounds and to correlate the data obtained with the clinical picture. Considering the high incidence of Staphylococcus aureus infections at the level of chronic ulcers, but also the problem of developing multi-drug resistance, we performed an in-depth study of this bacterial species, by analyzing the phenotypic and genotypic virulence profile of methicillin-resistant Staphylococcus aureus strains. The study revealed important differences regarding the clinical evolution and virulence profiles of microorganisms isolated from lower limb wounds, as well as between patients diagnosed with chronic venous ulcers and those with lesions of different etiology.